Cystic fibrosis therapy: from symptoms to the cause of the disease - T N. Kireeva; D. I. Zhigalina; N. A. Skryabin (Вавиловский журнал генетики и селекции, 2025)
Cystic fibrosis (CF) is a disease with a broad clinical and genetic spectrum of manifestations, significantly impacting the quality and duration of life of patients. At present, a diagnosis of CF enables the disease to be identified at the earliest stages of its development. The accelerated advancement of scientific knowledge and contemporary research techniques has transformed the methodology employed in the treatment of CF, encompassing a spectrum of approaches from symptomatic management to pathogenetic therapies. Pathogenetic therapy represents an approach to treatment that aims to identify methods of restoring the function of the CFTR gene. The objective of this review was to analyse and summarize the available scientific data on the pathogenetic therapy of CF. This paper considers various approaches to the pathogenetic therapy of CF that are based on the use of targeted drugs known as CFTR modulators. The article presents studies employing gene therapy techniques for CF, which are based on the targeted delivery of a normal copy of the CFTR gene cDNA to the respiratory tract via viral or non-viral vectors. Some studies have demonstrated the efficacy of RNA therapeutic interventions in restoring splicing, promoting the production of mature RNA, and increasing the functional expression of the CFTR protein. The review also analyzes literature data that consider methods of etiotropic therapy for CF, which consists of targeted correction of the CFTR gene using artificial restriction enzymes, the CRISPR/Cas9 system and a complex of peptide-nucleic acids. In a prospective plan, the use of cell therapy methods in the treatment of lung damage in CF is considered.